Ідейні цінності в правових принципах громадянського суспільства: історико-правовий аналіз - Лаба, О.; Laba, O. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано правове вчення про принципи громадянського суспільства, про плюралізм поглядів та ідеологій. Визначено особливості трансформації правової основи принципів громадянського суспільства сучасної України. Стаття присвячена деталізації загальних питань становлення громадянського суспільства, його існування, форм і перспектив розвитку як цілісного процесу і правового феномена. Визначено, що вітчизняні та зарубіжні вчені, досліджуючи правові принципи громадянського суспільства, зосереджують свою увагу: по-перше, на історії становлення і розвитку окремих напрямів теорії громадянського суспільства, по-друге, на ґрунтовній юридичній концептуалізації його сутності. The article considers the legal doctrine and the principles of civil society and pluralism of views and ideologies in it. The author defines the peculiarities of the transformation of the legal basis of the civil society principles in modern Ukraine. The article is devoted to clarifing general issues of civil society, its existence, forms and prospects of its development as a holistic process and legal phenomenon. It has been determined that that Ukrainian and foreign scholars examining the legal principles of civil society primarily lay emphasis on history of formation and development of certain areas of the theory of civil society and, secondly, on thorough legal conceptualization of its essence. Despite the specific way of formation of Ukrainian civil society, in general, the strategy of its development is similar to that of the Western civilization in the context of the gradual evolution to the standards of European democracy.
Ideological Values in the Legal Principles of Civil Society: Historical and Legal Analysis.
Keywords: громадянське суспільство; правові принципи; ідейні цінності; правова думка; законотворча діяльність; держава; право; громадянин; демократія; civil society; legal principles; ideological values; legal thought; legislative activity; state; law; citizen; democracy